DEVELOPING A POP UP BOOK TO TEACH READING NARRATIVE TEXT - Destriwanty Erria Nainggolan; Meisuri; Anggraini Thesisia Saragih (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2024)
The aim of this study was to develop a Pop Up Book as learning media for teaching reading narrative text for tenth grade students at SMA Swasta Raksana Medan. The research method that used in this study was Research and Development (R&D). The subject of this study was tenth grade students of SMA Swasta Raksana Medan. Questionnare was administrated to the teacher and students to get information about students’ need, existing media. It was found that 79% students said that they were bored learning English in reading skill by using textbook. 89% student said that the media that the teacher used was uninteresting and didn’t make significant improvement. 91% student said that they need an interesting, creative, and innovative media. 89% student said that the media that have been designed was appropriate to use. The instrument of collecting the data used questionnaire to experts from English teacher and English Lectrurer. Research Procedures was modified into five steps, they were: evaluation and need analysis, media design, validation, revision and final product. The product has been validated by experts (material and media). The data are analyzed by using descriptive technique. The product has been validated by material expert and media expert. For the first expert the media was 83% valid in material aspect, and 90% valid in media aspect. While from the second expert the media was 95% valid in material aspect and 100% valid in media aspect. Based on the validation result, the media develop media was very good and appropriate to be used for teaching reading for the tenth grade students of SMA Swasta Raksana Medan.